Hubungan Kepribadian Guru Dengan Minat Belajar Matematika Peserta Didik Kelas V SDN 26 Cakranegara Tahun Ajaran 2021/2022 - Rahmaputri, Olliviani; Zain, Irawan; Jiwandono, Ilham Syahrul (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This research aims to find out how the relationship between the personality of teachers to the interest in learning mathematics class V SDN 26 Cakranegara Kec. Sandubaya Mataram City. This study consists of two variables, namely the teacher's personality variable and the learning interest variable. This type of research is quantitative correlational. Correlation quantitative research is research that aims to find out the relationship (relationship) between variables. The sample in this study was 70 students of class V of SDN 26 Cakranegara, and two teachers of VA and VB classes. Data collection for this study used questionnaires distributed to respondents. The study was conducted for 6 days from August 3-9, 2021.  The results of the data analysis showed that the competence of the teacher's personality (X), making a significant contribution to the learning interest (Y) indicated by a correlation coefficient value of 0.99.While for this significant test showed that the rhitung obtained was greater than rtabel (0.99>0.235), at a significant level of 5%. it is obtained that the calculated r obtained is greater than the rtabel (0.99>0.235), at a significant level of 5%. Based on the results of the determination analysis showed that the teacher competency variable (X) contributed 98.1% to learning interest (Y). In this case Ho is rejected and Ha is accepted. From these results, there is a significant relationship between the competence of the teacher's personality and the interest in learning mathematics of class V students of SDN 26 Cakranegara Kec. Sandubaya Mataram City.